2016
DOI: 10.1111/cote.12240
|View full text |Cite
|
Sign up to set email alerts
|

Colour stripping of reactive‐dyed cotton by ozone treatment

Abstract: Trials have been carried out to investigate the efficiency of ozone treatment in the colour stripping of reactivedyed cotton fabrics. The trials were performed on a specially designed apparatus to inject ozone gas into the liquor passing through a perforated beam with fabric rolls on it, just like a beam dyeing machine with ozone venturi injection. Conventional reductive colour stripping was applied as the control treatment, and ozone treatment was applied for three different application times (15, 30, and 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…The longest ozonation time gives the best color stripping result. COD value of effluent from ozonation is less than that of conventional reductive treatment [47].…”
Section: The Photographs Of Fabrics Treated By Developed Methods (I: Omentioning
confidence: 90%
“…The longest ozonation time gives the best color stripping result. COD value of effluent from ozonation is less than that of conventional reductive treatment [47].…”
Section: The Photographs Of Fabrics Treated By Developed Methods (I: Omentioning
confidence: 90%
“…Three different pH values (3,5,7) were used for color removal. The pH of solutions was adjusted using different concentrations of phosphoric acid and/or caustic soda (laboratory grade).…”
Section: Color Removal From the Dyed Cotton Textilesmentioning
confidence: 99%
“…Application of ozone in several domains of textile finishing has been reported. These include reduction clearing of polyester dyed with disperse dyes [5], discharge printing of reactive-dyed cotton fabrics [6], color stripping of reactive dyes from cotton textiles [7], and bleaching of raw cotton textiles [8]. The industrial application of ozone has been limited to denim and garment washing only, and its application to other areas can be a scope of study [9].…”
Section: Introductionmentioning
confidence: 99%
“…Successful decolorisation of reactive dyes by ozone treatment has been reported in the literature [17,[20][21][22][23]. Furthermore, Eren et al [24] reported a successful study on colour discharge of reactive dyed cotton by ozone. From this, it was suggested that discharge printing should be performed by ozone if colour discharge of the reactive dyed cotton fabric can be achieved through selected patterns.…”
Section: Introductionmentioning
confidence: 99%